2005
DOI: 10.3168/jds.s0022-0302(05)72872-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Frozen Storage on the Proteolytic and Rheological Properties of Soft Caprine Milk Cheese

Abstract: Freezing and long-term frozen storage had minimal impact on the rheology and proteolysis of soft cheese made from caprine milk. Plain soft cheeses were obtained from a grade A goat dairy in Georgia and received 4 storage treatments: fresh refrigerated control (C), aged at 4 degrees C for 28 d; frozen control (FC), stored at -20 degrees C for 2 d before being thawed and aged in the same way as C cheese; and 3-mo frozen (3MF), or 6-mo frozen (6MF), stored at -20 degrees C for 3 or 6 mo before being thawed and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 18 publications
(27 reference statements)
3
28
0
1
Order By: Relevance
“…The hardness values of the QF ranged from 9.13 to 11.27 N; although not significantly different, cheeses made with 0e1% added salt tended to have the lowest values while the cheeses containing 1.5e2.5% added salt had the higher values. The hardness value for QF from bovine milk was within the range for soft caprine milk cheeses (Van Hekken, Tunick, & Park, 2005). Studies of Cheddar cheese have suggested that salt contents above 0.5% increase the hardness of the cheese by promoting interactions between proteins (Mistry & Kasperson, 1998;Pastorino et al, 2003).…”
Section: Rheological Propertiesmentioning
confidence: 98%
“…The hardness values of the QF ranged from 9.13 to 11.27 N; although not significantly different, cheeses made with 0e1% added salt tended to have the lowest values while the cheeses containing 1.5e2.5% added salt had the higher values. The hardness value for QF from bovine milk was within the range for soft caprine milk cheeses (Van Hekken, Tunick, & Park, 2005). Studies of Cheddar cheese have suggested that salt contents above 0.5% increase the hardness of the cheese by promoting interactions between proteins (Mistry & Kasperson, 1998;Pastorino et al, 2003).…”
Section: Rheological Propertiesmentioning
confidence: 98%
“…Todaro et al, (2011) reported different effects of freezing according to the species, for example goat milk is more affected by the length of the freezing period and the typology of defrosting than ovine and bovine milk. Van Hekken, Tunick & Park (2005) found no significant proteolysis during the refrigerated ageing of soft cheese.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, food control authorities require an analytical method to discriminate between fresh Mozzarella PDO cheese and Mozzarella produced from frozen intermediates, which are not produced according to the PDO manufacturing process. addition in cheeses obtained from bovine, goat and sheep species Pazzola et al, 2013;Van Hekken, Tunick & Park, 2005;Todaro, Scatassa, Alicata, Mazza & Caracappa, 2011;Zhang, Mustafa, Ng-Kwai-Hang & Zhao, 2006). In particular, according to Zhang et al (2006), good quality sheep cheese can be produced from ovine milk that is frozen at −15 and −25 °C for 6 months without affecting the cheese yield or composition.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested as an alternative method to extend the shelf-life of dairy products like cheeses (Lück, 1977). The effect of freezing on physicochemical and rheological properties of several varieties of full-fat or traditional cheeses was investigated in previous publications (Califano & Bevilacqua, 1999;Gravier, Zaritzky, & Califano, 2004;Kuo & Gunasekaran, 2003;Van Hekken, Tunick, & Park, 2005;Verdini, Zorrilla, & Rubiolo, 2002. However, the effect of freezing on the rheological behaviour of low-fat cheeses has not been extensively studied.…”
Section: Introductionmentioning
confidence: 98%